Selection of Energizing Quantities for Sensitive Ground Fault Protection of MV Electric Power Networks - Miedzinski, B.; Pyda, D.; Habrych, M. (Elektronika ir Elektrotechnika, 2012)
In the paper an approach to selection of energizing quantities applicable for the developed sensitive ground fault protection of MV networks is presented and results are discussed. The protection is operated basing on comparison of the argument difference value between selected harmonics of zero-sequence as voltage as well as current harmonics injected simultaneously. It was found that such correlations are particularly useful for successful detection of onerous high resistive ground faults. On the basis of simulation and investigated results the suitable conclusions if about application of proper quantities for practice were formulated. Ill. 11, bibl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2374